Kedudukan Negara sebagai Pemegang Saham Dwiwarna dalam Privatisasi Perusahaan Anggota Holding BUMN - Huta Disyon; Elisatris Gultom; Ema Rahmawati (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2023)
According to Government Regulation 72/2016, the formation of state-owned-holding-companies (“SOHC”) is accomplished using the transfer mechanism, which transforms State shares in SOEs into equity in other SOEs, resulting in a change in the status of share ownership of holding-member-companies from being owned directly by the State to being owned by the holding company. GR 72/2016 also requires the state to own shares with special rights in holding-members-companies originating from ex-SOE, which can only be owned by the state, known as Dwiwarna shares. Potential issues arise because of the ambiguity of the controlling authority role in managing a SOHC, whether the state still holds it or has been transferred to the parent company, including in terms of selling shares of holding-member-companies. Hopefully, this study will provide the State with legal certainty, benefits, and justice in privatizing holding-member companies. The research methodology used is a normative juridical approach with qualitative normative legal research that relies on secondary data from the library. This study indicates that the State’s Controlling Rights are based on state ownership of Dwiwarna shares in holding-member companies originating from ex-SOE, implying that the sale of company shares only sometimes results in reduced state control and ownership. As a result, the sale of series B shares may be accomplished using corporate regulations in line with their respective authorities. Meanwhile, the State must carry out the sale of Dwiwarna shares, per GR 33/2005. The author recommends that the State create a new mechanism for exercising Dwiwarna shareholder privileges so that the implementation of the absolute authority and rights for Dwiwarna shareholders can proceed in an orderly and legal manner.